Purulent pericarditis and septic shock secondary to a hepatic-pericardial fistula in a patient with complex oncologic and cardiac history - Cameron Rattray; Mohamad Moughnyeh; Jibran Fateh; Michael Lee (Journal of Cardiothoracic Surgery)
Abstract Background Hepatic-pericardial fistulas are extremely rare complications typically arising from hepatic abscesses, trauma, or invasive procedures. These fistulas can lead to clinical manifestations such as pericarditis, cardiac tamponade, and septic shock. We report a case of purulent pericarditis and septic shock secondary to a hepatic-pericardial fistula in a patient with complex cardiac and oncologic history. Case presentation A 76-year-old man with a history of pancreatic, renal cell and prostate cancer presented with acute chest pain and dyspnea. Initial investigations revealed a moderate pericardial effusion and a suspicious hepatic lesion. The patient developed cardiac tamponade and underwent emergency pericardiocentesis, draining 750 ml of purulent fluid. A CT-guided biopsy confirmed a hepatic abscess with fistulization to the pericardium. Despite antibiotic therapy and drainage procedures, the patient’s condition deteriorated, resulting in septic shock and death. Discussion This case highlights the challenges in managing hepatic-pericardial fistulas, particularly in patients with significant comorbidities. Bacteroides fragilis was identified as the causative pathogen, which underscores the importance of timely identification and management of these rare infections. Early surgical intervention and targeted antibiotic therapy are critical, although prognosis remains poor in patients with compromised cardiovascular and respiratory status. Conclusion Hepatic-pericardial fistulas, though rare, should be considered in patients with unexplained pericarditis or septic shock, particularly in the presence of hepatic abscesses. Early recognition, multidisciplinary management, and individualized treatment are essential to improve outcomes.